Community acceptance of services and effectiveness of health camps in high-risk areas of Karachi, Sindh, Pakistan, 2021 - Abbasi, Fayaz Hussain; Mehraj, Jaishri; Khowaja, Azeem; Sodhar, Irshad Ali; Chandio, Shoukat Ali; Rasool, Shumaila; Zardari, Asif Ali; Hussain, Imtiaz; Bosan, Altaf; Stuckey, Erin M.; Shaikh, Ahmed Ali (Frontiers in Public Health, 2025)
IntroductionHealth camps are organized to provide basic health services in underprivileged communities. This study was conducted to determine community acceptance and effectiveness of health camps in the high-risk areas for the polio program in Karachi, Pakistan.MethodsThis cross-sectional survey was conducted at the health campsites in high-risk union councils (HRUCs) of four districts of Karachi, Sindh. The survey was carried out in three rounds after a polio vaccination campaign in June, August, and October 2021. In June and August, health camps were organized in eight HRUCs; in October, the scope was extended to 33 union councils. All health camps provided basic health services, maternal and child health services, and routine immunization.ResultsIn June 877, August 367, and October 383 respondents participated in the survey. The main services availed include consultation with a doctor (64% in June, 79% in August, 78% in October), followed by childhood vaccination (58% in June, 55% in August, 69% in October), and nutrition support (34% in June, 17% in August, 17% in October). Children’s immunization increased from 80% in June to 86% in August and 96% in October health camp rounds. Among parents who do not allow oral polio vaccine from polio teams at their doorstep, also vaccinated children at the health camps 48 (81%) in June, eight (80%) in August, and 13 (87%) in October.ConclusionHealth camps played a crucial role in building the reputation of the polio program among underserved communities in Karachi’s high-risk areas. Alongside routine immunization vaccination services, the provision of public health services such as permanent healthcare facilities, access to safe drinking water, proper waste disposal, and mother and child healthcare services, are crucial steps toward improving immunization and overall health outcomes and strengthening community trust.